The Role of Brand Attachment Brand Perceived Quality and Consumer Satisfaction On Herborist Consumer Loyalty - Mangestuti, Ratna Mai; Kussudyarsana, Kussudyarsana (VISA: Journal of Vision and Ideas, 2024)
Examining the impact of customer happiness, Brand Attachment, and Brand Perceived Quality on customer loyalty is the main objective of this research. The demographics and sample for this study consist of people who live in Surakarta who have made purchases at Herborist. This quantitative research used a purposive sampling technique to obtain primary data from 150 participants who filled out questionnaires. To test the hypothesis, this research uses SPSS. Brand Attachment, Brand Perceived Quality, and Consumer Satisfaction are elements that are strongly correlated with customer loyalty, as shown in research. Respondents in this study can only choose from a limited set of alternatives specified in the questionnaire. Research findings regarding the influence of brand attachment, Brand Perceived Quality, and customer satisfaction on Herborist customer loyalty produce the following conclusions: Consumer Loyalty (Y) is positively and significantly influenced by Brand Attachment (X1). The relationship between consumer loyalty (Y) and brand perceived brand quality (X2) is positive and statistically significant. Customer loyalty (Y) and customer satisfaction (X3) have a positive and statistically significant link. Meanwhile, there is a positive and statistically significant relationship between consumer loyalty (Y), Brand Attachment (X1), and Brand Perceived Quality (X2).